Implementasi Etika Bisnis Syariah dalam Perusahaan Mikro dan Kecil di Indonesia: Tinjauan Hukum dan Praktik - Rina Widyaningsih (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2025)
Sharia business ethics are moral and legal principles that must be upheld by business actors, especially in micro and small companies that contribute significantly to the national economy. This study aims to examine how the implementation of sharia business ethics in micro and small companies in Indonesia from the perspective of law and real practices in the field. The research method uses a qualitative approach with field studies, in-depth interviews with business actors, and analysis of regulations governing sharia business ethics. The results of the study indicate that although there is awareness of the importance of sharia business ethics, its implementation is still limited by factors of knowledge, access to information, and unequal understanding of the law. In addition, obstacles in terms of financing and business management also affect the consistency of the application of sharia principles. The conclusion of the study emphasizes the need to strengthen education, coaching, and regulations that support micro and small companies to run their businesses according to sharia values ​​optimally. Recommendations are submitted for the government and related institutions to provide more concrete support through training, mentoring, and facilitation of access to sharia financing.